2021
DOI: 10.14814/phy2.15007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of renal olfactory receptor 1393 leads to improved glucose homeostasis in a type 1 diabetic mouse model

Abstract: Renal olfactory receptor 1393 (Olfr1393) is an understudied sensory receptor that contributes to glucose handling in the proximal tubule. Our previous studies have indicated that this receptor may serve as a regulator of the sodium glucose co‐transporters (SGLTs) and contributes to the development of glucose intolerance and hyperfiltration in the setting of diet‐induced obesity. We hypothesized that Olfr1393 may have a similar function in Type 1 Diabetes. Using Olfr1393 wildtype (WT) and knockout (KO) mice alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…Previous animal studies revealed an upregulation of SGLT2 expression in Akita and db/db mice [40,41]; however, it is currently controversial about the protein expression of SGLT2 in STZ-induced type 1 diabetic model [41–43]. We found no changes in SGLT2 expression after STZ treatment, which are consistent with a report by Schiazza et al [44]. Thus, HS-induced Na + imbalance and BP changes in STZ mice could not be attributed to changes in proximal tubular sodium reabsorption.…”
Section: Discussionsupporting
confidence: 91%
“…Previous animal studies revealed an upregulation of SGLT2 expression in Akita and db/db mice [40,41]; however, it is currently controversial about the protein expression of SGLT2 in STZ-induced type 1 diabetic model [41–43]. We found no changes in SGLT2 expression after STZ treatment, which are consistent with a report by Schiazza et al [44]. Thus, HS-induced Na + imbalance and BP changes in STZ mice could not be attributed to changes in proximal tubular sodium reabsorption.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, Olfr1393, expressed in the kidneys by the proximal tubules, has been confirmed to be involved in glucose reabsorption at renal level by increasing expression and membrane translocation of the sodiumglucose cotransporters SGLT1 and SGLT2 [40], thus increasing blood glucose levels and emerging indeed as an important contributor to T2DM development. Despite the molecular mechanism is not so clear, further studies have confirmed Olfr1393 capability to modulate SGLT1 and SGLT2: infact, SGLT2 expression was reduced in Olfr1393 KO mice, resulting in improvement of hyperglycemia and glucose tolerance [95], [96]. Both in vitro and in vivo studies revealed and increased expression of SGLT2, and thus of glucose reabsorption, in T2DM patients [97]:…”
Section: Ors and Glucose Metabolism In Human Disordersmentioning
confidence: 97%
“…In particular, Olfr1393, expressed in the kidneys by the proximal tubules, has been confirmed to be involved in glucose reabsorption at renal level by increasing expression and membrane translocation of the sodium-glucose cotransporters SGLT1 and SGLT2 [40], thus increasing blood glucose levels and emerging indeed as an important contributor to T2DM development. Despite the molecular mechanism is not so clear, further studies have confirmed Olfr1393 capability to modulate SGLT1 and SGLT2: infact, SGLT2 expression was reduced in Olfr1393 KO mice, resulting in improvement of hyperglycemia and glucose tolerance [95,96]. Both in vitro and in vivo studies revealed and increased expression of SGLT2, and thus of glucose reabsorption, in T2DM patients [97]: although not yet completely understood, it seems that SGLT2 overexpression should be due to a hyperphosphorilaton guided by insulin via PKA and PKC [98,99].…”
Section: Ors In Glucose Homeostasismentioning
confidence: 99%